See and read all these words : the concept of the written in the Book of Jeremiah - Eggleston, Chad L. (Siphrut ;, 2016)
"Unusually for the Hebrew Bible, the book of Jeremiah contains a high number of references to writers, writing, and the written word. The book (which was primarily written during the exilic period) demonstrates a key moment in the ongoing integration of writing and the written word into ancient Israelite society. Yet the book does not describe writing in the abstract. Instead, it provides an account of its own textualization, thereby blurring the lines between the texts in the narrative and the texts that constitute the book. Scrolls in Jeremiah become inextricably intertwined with the scroll of Jeremiah. To authenticate the book of Jeremiah as the word of YHWH, its tradents present a theological account of the chain of transmission from the divine to the prophet and then to the scribe and the written page. Indeed, the book of Jeremiah extends the chain of transmission beyond the written word to include the book of Jeremiah itself and, finally, a receiving audience. To make the case for this chain of transmission, See and Read's three exegetical chapters attend to writers (YHWH, prophets, and scribes), the written word, and the receiving audience. The written word, as Jeremiah imagines it, is to be received by a worshiping audience through public reading but delivered via textual intermediaries"--